The Effect of Open-market Retail Conditions in Nigeria on Oxidative Deterioration of Imported Frozen Upper Arms (Brachium) of Turkeys - Onibi, Gbenga Emmanuel (International Journal of Poultry Science, 2003)
The effect of different periods of display and/or storage, as practiced under retail conditions for frozen turkey upper arms in Nigerian open markets, on physical appearance, odour and extent of lipid peroxidation of the meat was investigated. Five batches of frozen turkey shipments, sampled bi-monthly at 45 upper arms per batch were used. The frozen upper arms from each batch were displayed on the counter for up to 3 days, but re-frozen overnight. Five samples from the same batch were removed at 6 hourly intervals, giving a total of 9 treatments per batch. The samples were assessed for physical quality attributes (appearance and odour) by a 7-member panel using a 9-point Hedonic scale. The turkey upper arms were dissected and the moisture and lipid contents of the muscles measured. Extent of oxidation of muscle was determined by quantifying the malonaldehyde (MDA) concentration using the thiobarbituric acid reactive substances test. Muscle, bone and skin were found to represent 65.05 ± 4.28, 23.51 ± 4.21 and 14.44 ± 2.49% by weight of the intact upper arms. The relationship between the intact upper arms and the skin, bone and muscle, as measured by the correlation coefficient were found to be 0.60, 0.50 and 0.95 respectively (P